Evaluating temporal bone column density for optimized bone conduction implant placement - Talon, Emile; Wagner, Franca; Weder, Stefan; Anschuetz, Lukas; Caversaccio, Marco; Wimmer, Wilhelm (Frontiers in Surgery, 2023)
Introduction: An optimal placement of bone conduction implants can provide more efficient mechanical transmission to the cochlea if placed in regions with greater bone column density. The aim of this study was to test this hypothesis and to determine the clinical potential of preoperative bone column density assessment for optimal implant placement.Methods: Five complete cadaver heads were scanned with quantitative computed tomography imaging to create topographic maps of bone density based on the column density index (CODI). Laser Doppler vibrometry was used to measure cochlear promontory acceleration under bone conduction stimulation in different locations on the temporal bone, using a bone-anchored hearing aid transducer at frequencies ranging from 355 Hz to 10 kHz.Results: We found a statistically significant association between CODI levels and the accelerance of the cochlear promontory throughout the frequency spectrum, with an average increase of 0.6 dB per unit of CODI. The distance between the transducer and the cochlear promontory had no statistically significant effect on the overall spectrum.Discussion: We highlight the importance of bone column density in relation to the mechanical transmission efficiency of bone conduction implants. It may be worthwhile to consider column density in preoperative planning in clinical practice.